2014
DOI: 10.1186/2041-9139-5-47
|View full text |Cite
|
Sign up to set email alerts
|

What determines a leaf's shape?

Abstract: The independent origin and evolution of leaves as small, simple microphylls or larger, more complex megaphylls in plants has shaped and influenced the natural composition of the environment. Significant contributions have come from megaphyllous leaves, characterized usually as flat, thin lamina entrenched with photosynthetic organelles and stomata, which serve as the basis of primary productivity. During the course of evolution, the megaphylls have attained complexity not only in size or venation patterns but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 149 publications
0
43
0
Order By: Relevance
“…High AGL79 transcript levels altered leaf lamina shape in the AGL79OE plants, which was similar to the effect of SPL10 overexpression (Figure 4D). During leaf development, PIN1 and KNOX1 are known to regulate leaf initiation, HD-ZIPIII, KANADI , and YABBY mediate leaf outgrowth, and ANGUSTIFOLIA3 and GROWTH-REGULATING FACTOR5 specify leaf expansion and maturation, while APUM23 is also critical for determining leaf polarity (Dkhar and Pareek, 2014). It remains elusive whether AGL79 and SPL10 determine leaf shape in concert with the afore-mentioned plant leaf shape determination factors.…”
Section: Discussionmentioning
confidence: 99%
“…High AGL79 transcript levels altered leaf lamina shape in the AGL79OE plants, which was similar to the effect of SPL10 overexpression (Figure 4D). During leaf development, PIN1 and KNOX1 are known to regulate leaf initiation, HD-ZIPIII, KANADI , and YABBY mediate leaf outgrowth, and ANGUSTIFOLIA3 and GROWTH-REGULATING FACTOR5 specify leaf expansion and maturation, while APUM23 is also critical for determining leaf polarity (Dkhar and Pareek, 2014). It remains elusive whether AGL79 and SPL10 determine leaf shape in concert with the afore-mentioned plant leaf shape determination factors.…”
Section: Discussionmentioning
confidence: 99%
“…Both cytokinin and auxin can trigger alterations in leaf morphology (Efroni et al, 2010;Byrne, 2012). For instance, high auxin concentration leads to the activation of COTYLEDON CUP-SHAPED2 (CUC2), which in turn establishes adult patterns in Arabidopsis leaves (Bilsborough et al, 2011;Byrne, 2012;Dkhar and Pareek, 2014). Moreover, increasing expression of YUCCA genes (which have a pivotal role in the tryptophan-dependent auxin biosynthesis pathway; Hentrich et al, 2013) is correlated with increases in age and leaf complexity of the tree Gevuina avellane (Ostria-Gallardo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The grapevine genus is well-known for extensive within and among-species variation in leaf shape 19,20 . Previous work demonstrated that the genetic underpinnings of leaf shape are evolutionarily conserved within species, while developmental constraints and environmental influences such as light, temperature, and water availability affect leaf shape variation among genotypes and within individuals 2123 . We collected leaves from approximately the same developmental stage (i.e.…”
Section: Discussionmentioning
confidence: 99%